OP17 Assessment of symptom prevalence in patients with decompensated cirrhosis using a novel Liver Integrated Palliative Outcome Score (Liver iPOS). (20th September 2022) - Beck, Hannah; Dhar, Ameet; Selvapatt, Nowlan; Lewis, Heather; O'Dell, Carrieanne; Buxton, Katherine; Atkinson, Stephen; Possamai, Lucia
Abstract : Background: There is a paucity of data on subjective illness-related concerns of patients with decompensated cirrhosis (DC). Clinician recognition of symptom burden may be poor, subsequently, patients are under-referred to supportive services such as early palliative care. The Integrated Palliative Outcome Score (iPOS) is a patient-reported outcome measure (PROM) in widespread use and has been adapted for other end-stage diseases. Objectives: To adapt and trial a liver-specific iPOS to: (1) Measure patient reported symptom prevalence in inpatients (IP) and outpatients (OP) with DC. (2) Pilot the feasibility of implementing the Liver iPOS in OP clinics. Methods: A liver-specific adaption to iPOS was made based on pilot data, adding high prevalence and removing low prevalence symptoms. Adult patients with DC, Child-Pugh ≥ 7, were recruited at a London Hospital. Inpatients conducted the liver iPOS during admission. Outpatients to whom the iPOS was not applied were used to measure baseline patient satisfaction with a two-question survey and Likert scale (out of 5). Consultations were timed. A further group of sequentially recruited outpatients were offered iPOS questionnaires before their consultation. Patient satisfaction was measured and consultations were timed. Qualitative feedback was obtained from participating consultants and patients. Results: Overall 64 patients (43 OP and 21 IP) participated; 77% of subjects were male and 42% had English as a first language. The most common aetiology was alcohol related liver disease (81% IP, 65% OP). A greater proportion of IP had Child Pugh scores of C (62%) than Outpatients (21%). 21 inpatients and 29 outpatients completed a Liver iPOS. Results demonstrated a high burden of physical ( figure 1 ) and psychosocial symptoms among IP and OP. 53% of IP and 34% of OP reported anxiety 'most of the time' or 'always'. Sleep disturbance was graded as 'severe' or 'overwhelming' by 47% of IP and 50% of OP. Symptoms added to iPOS for liver-specific adaptation were high prevalence (≥ moderate intensity in >50%). Patient satisfaction with OP consultations was 9.8 (max 10) both with and without the liver iPOS. Average consultation length showed a non-significant increase from 16 to 18 minutes. Qualitative feedback on the utility and feasibility of liver iPOS implementation was positive. Discussion: The novel Liver iPOS revealed a high symptom burden and underlined the need to improve supportive care. In this small pilot study, the liver iPOS was a feasible PROM to implement in OP and IP settings.